Analysis of the modifying effects of SAA1, SAA2 and TNF-alpha gene polymorphisms on development of amyloidosis in FMF patients - Yilmaz, Engin; Balci, Banu; Kutlay, Sim; Ozen, Seza; Ertürk, Sensuvar; Oner, Ayse; Beşbaş, Nesrin; Bakkaloğlu, Ayşin (The Turkish Journal of Pediatrics, 2003)
The aim of this study was to examine whether polymorphisms at serum amyloid A (SAA) and tumor necrosis factor-alpha (TNF-alpha) genes are associated with development of amyloidosis in familial Mediterranean fever (FMF) patients. Seventy-three FMF patients with amyloidosis and 100 other FMF patients without amyloidosis of known genotypes and 100 healthy control subjects were analyzed. There was a significant difference in the frequency of alpha/alpha genotype at the SAA1 locus between FMF patients with amyloidosis and controls and FMF patients without amyloidosis. The frequencies of the alpha/alpha genotype and alpha alleles at SAA1 locus were significantly higher in the FMF patients with amyloidosis. The frequencies of the alpha allele at SAA1 locus in FMF patients with amyloidosis, without amyloidosis and controls were 85.6%, 49.5% and 42.5%, respectively. We demonstrated that alpha/alpha genotype at SAA1 gene might have modifying effects on the development of amyloidosis. Determination of genotypes at SAA1 locus can play a key role in conferring genetic susceptibility and patient’s prognosis to renal amyloidosis.